Deficiency of MAPK-activated protein kinase 2 (MK2) prevents adverse remodelling and promotes endothelial healing after arterial injury - Kapopara, Piyushkumar R.; Felden, Johann von; Soehnlein, Oliver; Wang, Yong; Napp, L. Christian; Sonnenschein, Kristina; Wollert, Kai C.; Schieffer, Bernhard; Gaestel, Matthias; Bauersachs, Johann; Bavendiek, Udo (Thrombosis and Haemostasis, 2014)
Maladaptive remodelling of the arterial wall after mechanical injury (e. g. angioplasty) is characterised by inflammation, neointima formation and media hypertrophy, resulting in narrowing of the affected artery. Moreover, mechanical injury of the arterial wall causes loss of the vessel protecting endothelial cell monolayer. Mitogen-activated protein kinase (MAPK)-activated protein kinase 2 (MK2), a major downstream target of p38 MAPK, regulates inflammation, cell migration and proliferation, essential processes for vascular remodelling and reendothelialisation. Therefore, we investigated the role of MK2 in remodelling and reendothelialisation after arterial injury in genetically modified mice in vivo. Hypercholesterolaemic low-densitylipoprotein- receptor-deficient mice (ldlr-/-) were subjected to wire injury of the common carotid artery. MK2-deficiency (ldlr-/-/mk2-/-) nearly completely prevented neointima formation, media hypertrophy, and lumen loss after injury. This was accompanied by reduced proliferation and migration of MK2-deficient smooth muscle cells. In addition, MK2-deficiency severely reduced monocyte adhesion to the arterial wall (day 3 after injury, intravital microscopy), which may be attributed to reduced expression of the chemokine ligands CCL2 and CCL5. In line, MK2-deficiency significantly reduced the content of monocytes, neutrophiles and lymphocytes of the arterial wall (day 7 after injury, flow cytometry). In conclusion, in a model of endothelial injury (electric injury), MK2-deficiency strongly increased proliferation of endothelial cells and improved reendothelialisation of the arterial wall after injury. Deficiency of MK2 prevents adverse remodelling and promotes endothelial healing of the arterial wall after injury, suggesting that MK2-inhibition is a very attractive intervention to prevent restenosis after percutaneous therapeutic angioplasty.
Keywords: Arterial remodelling; reendothelialisation; MK2; inflammation; leukocytes